A Comprehensive Survey on Arithmetic Optimization Algorithm - Dhal, Krishna Gopal; Sasmal, Buddhadev; Das, Arunita; Ray, Swarnajit; Rai, Rebika (Archives of computational methods in engineering, 2023)
Arithmetic Optimization Algorithm (AOA) is a recently developed population-based nature-inspired optimization algorithm (NIOA). AOA is designed under the inspiration of the distribution behavior of the main arithmetic operators in mathematics and hence, it also belongs to mathematics-inspired optimization algorithm (MIOA). MIOA is a powerful subset of NIOA and AOA is a proficient member of it. AOA is published in early 2021 and got a massive recognition from research fraternity due to its superior efficacy in different optimization fields. Therefore, this study presents an up-to-date survey on AOA, its variants, and applications.